Skenaoutfit As Digital Rituals:Tribal Branding In Kalcer Culture On Tiktok - Amartya Citra Kevina Soepangat; Siska Armawati Sufa; Iwan Joko Prasetyo; Zulaikha Zulaikha (UNIVED Press, 2026)
This study investigates the role of digital rituals and tribal branding within the #SkenaOutfit phenomenon on TikTok, focusing on how Indonesian youth express cultural identity through symbolic practices. Employing a quantitative approach with Social Network Analysis (SNA), the research examines user interactions surrounding the hashtag #SkenaOutfit from 2022 to 2025. The data, extracted from publicly accessible TikTok content, includes posts, mentions, duets, and hashtags. Analysis reveals a low-density, high-modularity network, indicating fragmented yet symbolically cohesive communities. Influential accounts such as @zuceiy and @kaaarsa serve as central nodes connecting stylistic subgroups. Although user connectivity is limited, interactions such as tagging and posting function as digital rituals that reinforce Kalcer identity. The findings demonstrate how TikTok users participate not in dialogue, but in symbolic performativity that strengthens subcultural bonds. By integrating Ritual Theory, Actor-Network Theory, and Social Network Theory, this study uncovers how fashion, algorithms, and platform design co-construct collective identity. The research contributes to understanding digital tribalism and the symbolic infrastructure of online communities, offering implications for marketers, content creators, and cultural analysts interested in youth subcultures and algorithm-driven branding practices.